2001
DOI: 10.1016/s0378-1097(00)00508-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the fresh water cyanobacterium Anabaena variabilis SPU 003 and its application for oxygen-free hydrogen production

Abstract: Photoproduction of hydrogen has been studied as one of the ways to produce a clean, renewable energy source. Ultrastructure of the selected strain Anabaena variabilis SPU 003, a heterocystous cyanobacterium, has been done to understand the cell structure. The organism was found to be essentially a dark hydrogen producer. While pH had no significant effect on hydrogen production, optimum temperature was found to be 30³C. Various sugars increased the production of hydrogen while the presence of various nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
9
1
1
Order By: Relevance
“…The results of this study are different from that obtained by Shah et al (2001), who showed a decline in hydrogen production by cyanobacteria in the presence of dyes. Variable results also have been reported on growth and photosynthesis of green algae and cyanobacteria with respect to heavy metals (Whitton 1970;Takamura et al 1989;Horcsik et al 2006).…”
Section: Tolerance Studiescontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are different from that obtained by Shah et al (2001), who showed a decline in hydrogen production by cyanobacteria in the presence of dyes. Variable results also have been reported on growth and photosynthesis of green algae and cyanobacteria with respect to heavy metals (Whitton 1970;Takamura et al 1989;Horcsik et al 2006).…”
Section: Tolerance Studiescontrasting
confidence: 99%
“…Some earlier studies on cyanobacteria, however, reported reduced hydrogen production in the presence of dyes (e.g. Shah et al 2001). …”
Section: Tolerance Studiesmentioning
confidence: 93%
“…Interestingly, nitrogen-fixing cells of A. variabilis SPU 003 have the capacity to produce hydrogen mainly in darkness (181). Addition of various sugars stimulated the production of hydrogen, with mannose giving the highest rate, 5.58 nmol of hydrogen produced per mg dry weight per h (181).…”
Section: Rates Of Cyanobacterial Hydrogen Productionmentioning
confidence: 99%
“…Interestingly, nitrogen-fixing cells of A. variabilis SPU 003 have the capacity to produce hydrogen mainly in darkness (181). Addition of various sugars stimulated the production of hydrogen, with mannose giving the highest rate, 5.58 nmol of hydrogen produced per mg dry weight per h (181). Since the hydrogen production is the result of hydrogen evolution catalyzed by nitrogenase and a hydrogen consumption catalyzed mainly by an uptake hydrogenase, the obvious improvements are to increase the hydrogen production by using alternative nitrogenases and by inhibiting the activity of the uptake hydrogenase.…”
Section: Rates Of Cyanobacterial Hydrogen Productionmentioning
confidence: 99%
“…The cyanobacterium Anabaena variabilis has been studied extensively for its high potential of H 2 production and N 2 fixation and is regarded as potential candidate for future development of biologically produced clean energy, H 2 (Borodin et al 2000;Vyas and Kumar 1995;Shah et al 2001). It is also important in global carbon sequestration via photosynthetic CO 2 fixation (Nyhus et al 1993).…”
Section: Introductionmentioning
confidence: 99%